PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP STRATEGI KINERJA KARYAWAN - Rosi Sri Rahayu; Dewi Yulyasari; Immanuella Deryl Tyvado; Aliya Ananda Putri (CV. Multi Kreasi Media, 2023)
The main objective of this scientific article is to identify, explain and conduct an analysis study of the influence of transformational leaders and the work environment on employee performance strategies. The research method used in writing this article is to use the literature review method by collecting several article reference materials to review and analyze the contents of the topic of discussion that has the same correlation with the research article being studied. Based on the results of the analysis and interpretation of the results of the research article, a conclusion can be drawn that the type of transformational leadership is a suitable leadership style to be applied by a leader in the present/digitalization period which tends to be oriented towards employee development and providing massive motivation also proves that the work environment plays a role in building employee performance strategies which simultaneously have an influence on employee performance strategies.